Competency Models and Approaches in Management - Venkat Rathnam, Prof. B.; Suresh, A.; Sathish, K. (Prabandhan: Indian Journal of Management, 2008)
In a continuously changing environment, it has become impossible to manage successfully without sustained personal development. The managers of organizations face the globalization of business, rapid technological change, continual reorganizing and competence-based competition. These developments challenge the skills, competencies and capabilities of managers in organizations. In light of these dynamic changes, managers' competencies also need to be renewed on a regular basis. The concepts of skills, competencies and capabilities are all applied when discussing management development. Their definitions, however, seemingly remain unclear.